The relationship between self-efficacy and error orientation of nursing students during clinical internships: a cross-sectional study - Guo, Yuanli; Fan, Wenfeng; Dong, Xiaofang; Yang, Caixia; Wang, Min; Gao, Huanhuan; Lv, Peihua; Ma, Keke (Frontiers in Public Health, 2024)
Nursing students are an important source of clinical nursing errors because of their lack of clinical experience and error orientation could reveal their attitude and behavioral tendencies facing nursing errors. Understanding how the self-efficacy, motivation and security influence the error orientation of nursing students was important to develop measurements to enhance it.To explore the relationship between self-efficacy, motivation and error orientation of nursing students in clinical internship.This was a cross-sectional study. The electronic questionnaire was distributed to nursing students from September 14, 2023 to September 30 in a comprehensive tertiary A teaching hospital in Zhengzhou, Henan province. The instruments used in this study included General information questionnaire, General Self-efficacy Scale, Achievement Motives Scale, Security Scale, and Error Orientation Scale. SPSSAU was used to perform statistical description, mediation analysis and moderated mediation analyses.Results 510 nursing students were included in this study. The motivation for success and failure-escaping totally mediated the relationships between self-efficacy and error orientation of nursing students with a mediation effect of 0.101 (95% CI: 0.058~0.144). The security of nursing students moderated the direct effect of this model and the indirect effect of motivation for failure-escaping. When the security was at a high level, the self-efficacy of nursing students was positively correlated with their error orientation with the effect of 0.059 (95% CI: 0.003~0.116). When the security was at high level, the moderation effect was significant with the effect of -0.012 (95% CI: -0.026~-0.002), while when the security was at low and median levels, the mediation effect was non-existent .The motivation for success and failure-escaping plays different roles in the paths between self-efficacy and error orientation. The clinical nursing teachers should take measures to enhance the motivation for success but reduce the failure-escaping motivation to improve the error orientation of nursing students. Besides, it is also very important to pay attention to and improve the sense of security of students during clinical internships.